PERAN OPERATOR TERMINAL DALAM PENEGAKAN STANDAR PELAYANAN MINIMAL ANGKUTAN UMUM - Asya’ari, Imam; Marwiyah, Siti; Aribawa, Muhammad Yustino (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
The importance of the role of terminal operators in enforcing Minimum Service Standards (SPM) for public transportation in order to create safe, comfortable, and affordable transportation for the community. The issues raised are how SPM is implemented in type A terminals and how terminal operators play a role in enforcing these standards. The method used in this study is normative juridical with a legislative and conceptual approach. The results show that the implementation of SPM at terminals is not yet optimal, as indicated by the large number of facilities and infrastructure that do not meet standards, as well as a lack of awareness among operators and service users of the importance of service standards. Terminal operators play a role in supervision, provision of facilities, and education for service users, but face obstacles such as limited budgets, human resources, and policy synchronization between agencies. Therefore, it is necessary to strengthen regulations, increase human resource capacity, and collaborate between agencies in order to realize public transportation services that meet minimum standards